Caracterização mineralógica e gênese de latossolo em Marechal Cândido Rondon-PR - Marcolin, Luciane (2015)
The following work had as its goal to comprehend the evolution of the pedological cover and the active pedogenetic processes in the landscape unities in Marechal Cândido Rondon/PR. It has been selected two profiles of Oxisol, one under native vegetation and the other under agriculture. Through mineralogical analyses, allied with chemical, physical and morphological data, it was possible to interpret the current level of weathering of the soil profiles. Also, aiming to contribute with the studies about the geomorphic surfaces in the southwest of Paraná, it has been investigated the hypothesis of these surfaces' continuities in the west region of Paraná. The correlation between the results of this research and those from the studies which have already been done by the Grupo Gênese e Evolução de Superfícies Geomórficas e Formações Superficiais (GESGFS) point out that the studied soils in the west of Paraná are in advanced stage of weathering, presenting a mineralogy composed mainly by minerals 1:1 (Kaolinite), the minerals 2:1 (Vermiculite with hydroxy-interlayered). The mineralogy and other Oxisols attributes studied indicate that it has been occurred a process of monossialitization with partial hydrolysis along the pedogenesis. Considering the local landscape, the soil is in accordance with the formation environment in subtropical climate and in relation to the regional landscape they present the same pedological characteristics of the soils in the Incompletely Planed Surfaces V and VI in the southwest of PR, indicating that there is pedogenetic similarity between the soils from these surfaces and the studied soils.